2020
DOI: 10.31584/jhsmr.2020766
|View full text |Cite
|
Sign up to set email alerts
|

Normal Reference Ranges of Serum Testosterone and Gonadotropins in Thai Fertile Men: A Cross-sectional Study in a Single Tertiary Center

Abstract: Objective: To identify the normal reference ranges of serum testosterone and gonadotropins in Thai fertile men, compare these levels among different age groups, and assess their relationships with body mass index (BMI). Material and Methods: One hundred and twenty men aged 18-65 years whose wives had conceived within the past year were recruited at Songklanagarind Hospital and stratified into 3 age groups: 18-29, 30-39, and 40-65 years. Serum total testosterone (TT) was measured by electrochemiluminescence imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…A recent study reported that the normal reference range of the serum testosterone level is 2.1–9.7 ng/mL in fertile men ( n = 120) [ 40 ]. In our study, the mean testosterone level was 6.5 ng/mL among male farmworkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that the normal reference range of the serum testosterone level is 2.1–9.7 ng/mL in fertile men ( n = 120) [ 40 ]. In our study, the mean testosterone level was 6.5 ng/mL among male farmworkers.…”
Section: Discussionmentioning
confidence: 99%
“…This is slightly higher than the mean level in the previous report (4.8 ng/mL). Most participants in the previous study were overweight or obese and a negative correlation between BMI and the testosterone level has been reported [ 40 , 41 ]. Furthermore, an epidemiological study reported that the mean testosterone levels in Thai male farmers and Venezuelan farmworkers were 7.4 and 6.7 ng/mL, respectively, which is similar to the level in our study [ 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%